An Adaptable Luminescence Resonance Energy Transfer Assay for Measuring and Screening Protein-Protein Interactions and their Inhibition - Yapici, Engin (2012)
Protein–protein interactions (PPIs) are central to biological processes and represent an important class of therapeutic targets. Here we show that the interaction between FK506 binding protein 12 fused to green fluorescent protein (GFP-FKBP) and the rapamycin-binding domain of mTor fused to Escherichia coli dihydrofolate reductase (FRB-eDHFR) can be sensitively detected (signal-to-background (S:B) >100) and accurately quantified within an impure cell lysate matrix using a luminescence resonance energy transfer (LRET) assay. Ascomycin-mediated inhibition of GFP-FKBP/rapamycin/FRB-eDHFR complex formation was also detected at high S:B (>80) and Z’-factor (0.89). The method leverages the selective, stable binding of trimethoprim (TMP)-terbium complex conjugates to eDHFR, and time-resolved, background-free detection of the long-lifetime (~ms) terbium-to-GFP LRET signal that indicates target binding. TMP/eDHFR labeling can be adapted to develop high-throughput screening assays and complementary, quantitative counter-screens for a wide variety of PPI targets with a broad range of affinities that may not be amenable to purification.